Deciphering PPARγ activation in cardiometabolic syndrome: studies by in silico and in vivo experimental assessment. (4th March 2018) - Agrawal, Rohini; Nath, Virendra; Kumar, Harish; Kumar, Vipin
Abstract: Cardiometabolic syndrome (CMetS) is a consolidation of metabolic disorders characterized by insulin resistance, dyslipidemia and hypertension. Curcumin, a natural bioactive compound, has been shown to possess notable anti-oxidant activity and it has also been included as a super natural herb in the super natural herbs database. Most of the beneficial effects of Curcumin are possibly due to activation of the nuclear receptor, peroxisome proliferator-activated receptor gamma (PPARγ). The present study investigates molecular interactions of curcumin with PPARγ protein through molecular docking and molecular dynamics (MD) simulation studies. Further, effect of curcumin on high fat diet induced CMetS was studied in rats along with western blot for PPARγ and nuclear factor-κB (NF-κB) expressions and histopathological studies. Computational studies presented several significant molecular interactions of curcumin including Ser289, His323, His449 and Tyr473 of PPARγ. The in vivo results further confirmed that curcumin was able to ameliorate the abnormal changes and also, increased PPARγ expressions. The results confirm our hypothesis that activation of PPARγ by curcumin possesses the therapeutic potential to ameliorate the altered levels of metabolic changes in rats in the treatment of CMetS. This is the first report of CMetS treatment by curcumin and study of its underlying mechanism through in silico as well as in vivo experiments. Graphical Abstract: